Liability for Negligently Performed Financial Services: An Economic Theory - Palmer, James D (Victoria University of Wellington Law Review, 1996)
The law governing the recovery of negligently inflicted pure economic losses is complex and confusing. This article focuses on pure economic losses caused by negligently performed financial services, and considers whether a "law and economics" approach provides a superior framework for analysing the desirability of imposing negligence liability than that provided by traditional legal analysis. The article first discusses the law regarding negligently performed financial services and critiques the legal reasoning used to justify restricted liability. The author then introduces the law and economics approach to negligence liability. The special considerations which apply when a loss is purely economic and caused by a carelessly performed financial service are then analysed. Finally, a rule of discovery based on the economic analysis is presented, and its application is discussed with respect to some of the leading cases. The author concludes that the economic approach provides a powerful set of tools capable of explaining the major decisions in this area in terms of economic efficiency and wealth maximisation. It provides a clearer understanding of the factors that determine what the appropriate restrictions are, and is thus more convincing for determining liability than traditional legal analysis.